الدين بوصفه قيمة أخلاقية : منهج التز كية وضورة استعادته في حياتنا المعا صرة - محمد حلمي عبد الوهاب (Universiti Sains Islam Malaysia, 2016)
This article discusses the importance of religious teaching in developing the ethical value. Religious teaching is able to unite various ideologies through fulfilling their psychological need especially the feeling of togetherness. The ethical values in Islam are based on several foundations that the key element is the belief in Allah and judgement day. This article indicates the importance of the feeling of constant observant by Allah that available in human soul. If a believer controls his heart and remembers his God, he will reach at a level where he can see the impact of that feeling in his heart, body and actions. Therefore, in this period of time we are in need of spiritual revolution in our soul to become the foundation for our ethical value.